Multi‐Omics Analyses Reveal Relationships Between Gut Microbiota and Frailty - Xinlei Hou; Luwen Zhu; Jiongliang Zhang; Xinyue Li; Donghui Yu; Yuting Wang; Yumeng Su; Xiangyu Wei; Hanwen Ma; Wenjing Song; Jinting Li; Lili Teng; et al. (Brain and Behavior, 2025)
Abstract Introduction Observational studies suggest a strong association between gut microbiota and frailty, but the underlying mechanisms remain unclear. This study aimed to investigate potential causal links and biological pathways linking gut microbiota and frailty. Methods We utilized summary‐level data of gut microbiota and frailty data from MiBioGen and a genome‐wide association meta‐analysis. A bidirectional, two‐sample Mendelian randomization (MR) analysis was performed to investigate the causal relationship between gut microbiota and frailty. Additional genetic and genomic analyses were conducted to identify common biological pathways. Results We identified eight causal relationships between the gut microbiota composition and frailty. Inverse‐variance weighting suggested that genetic liability for the class Betaproteobacteria and genera Allisonella, Bifidobacterium, Clostridium innocuum, and Eubacterium coprostanoligenes was associated with increased frailty risk. In contrast, the class Bacteroidia, genus Eubacterium ruminantium, and the order Bacteroidales were associated with decreased risk. Reverse MR analysis provided no evidence for a causal effect of frailty on gut microbiota composition. In addition, TET2 was identified as a key hub gene associated with frailty, potentially linking gut microbiota to immune dysregulation and aging‐related inflammatory pathways. Conclusions Our findings provide genetic evidence that gut microbiota composition influences frailty risk and highlight TET2 as a potential mechanistic link via immune dysregulation. These results suggest that microbiota‐targeted interventions may offer novel strategies for the prevention and management of frailty in older adults.